Plant-Available Phosphorus after Application of Synthetic Chelating Agents. Issue 4 (21st February 2016) - Edwards, C. L.; Maguire, R. O.; Alley, M. M.; Thomason, W. E.; Whitehurst, G. B.
ABSTRACT: Fertilizer phosphorus (P) can become immobilized in acidic soils through bonds with iron (Fe) and aluminum (Al). Two chelating agents, ethylenediamine tetraacetic acid disodium salt (EDTA) and hydroxyethyl ethylenediamine triacetic acid (HEEDTA), were tested in a greenhouse study for efficiency at increasing plant-available P to corn ( Zea mays L.). Fertilizer P was added with or without chelate to the center of pots, simulating a starter band of P. Without the presence of chelates, biomass above and below ground increased linearly as P fertilizer rates increased at 0, 9.6, 19.3, 28.9, and 38.5 kg P ha −1 . Applications of EDTA and HEEDTA did not significantly increase water-soluble P (WSP), Mehlich 1 P, and Mehlich 3 P compared to soils without chelates. Applications of EDTA increased P uptake in the belowground biomass. Despite previous research showing that chelates increased WSP in soils, a decrease in P sorption was not observed with the additions of chelating agents to soils.